Wybrane zagadnienia postępowania dowodowego w sprawach z zakresu ubezpieczeń społecznych w świetle orzecznictwa sądowego - Prusinowski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Evidentiary proceedings in cases in the field of social insurance show significant autonomy in relation to the general model of proceedings in civil cases. However, the extent of possible deviations is not always clearly defined. The question of modifying the pattern of evidence in this category of cases is particularly problematic. In jurisprudence there has been adiscrepancy, which leads to regionalization of litigation attitude. Moreover, the position of the Supreme Court is also unclear. As aresult, it is necessary to take interpretative effort to create afocused directive to unify the course of evidentiary proceedings in cases in the field of social insurance.
Keywords: social insurance; evidentiary proceedings